2014
DOI: 10.1021/ac500753f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Spectroscopy Study on Polymerization of l-Lysine on Electrode Surface and Its Application for Immobilization and Detection of Suspension Cells

Abstract: Poly-L-lysine (PLL), which has been employed as a conductive polymer in the construction of some electrochemical sensors, can be prepared using L-lysine by cyclic voltammetry (CV) with a wide potential range. However, the presented explanation and description about its polymerization mechanism seems oversimplified because the self-reaction of electrode and the electrolysis of solvent at high potential are ignored. This work presents an intensive investigation on the relevant reactions during the process of PLL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Electrochemical impedance spectroscopy (EIS) has attracted growing interest in the last few years, not only because it is one of the most valuable tools for investigating the electrochemical interface, but also because it provides a promising platform for developing chemical sensors and biosensors. 1 6 When applying a perturbing sinusoidal voltage to the electrochemical system and recording the corresponding current responses as a function of frequency, many complex chemical and electrical processes could be described with equivalent circuits consisting of purely electrical terms. Therefore, EIS has been widely used in different applications ranging from the determination of double layer capacitance to monitoring zeolite formation, 7 studying the degradation of anticorrosion polymer coatings, 8 and examining the relationship between basic electrochemistry and actual battery performance.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) has attracted growing interest in the last few years, not only because it is one of the most valuable tools for investigating the electrochemical interface, but also because it provides a promising platform for developing chemical sensors and biosensors. 1 6 When applying a perturbing sinusoidal voltage to the electrochemical system and recording the corresponding current responses as a function of frequency, many complex chemical and electrical processes could be described with equivalent circuits consisting of purely electrical terms. Therefore, EIS has been widely used in different applications ranging from the determination of double layer capacitance to monitoring zeolite formation, 7 studying the degradation of anticorrosion polymer coatings, 8 and examining the relationship between basic electrochemistry and actual battery performance.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be concluded that the steric hindrance of the substituent affects the active site of radicals on the surface of the electrode during the amine oxidation process. The bonding reaction requires protons to be detached from the amine cation radical, so this reaction path is not feasible for tertiary amines [38]. Ethylenediamine is a typical aliphatic diamine, which exhibits characteristics of both primary and secondary amines.…”
Section: Resultsmentioning
confidence: 99%
“…The wide linear range of 2.0 × 10 2 −2.0 × 10 8 cells mL −1 (equivalent to 2.0 − 2.0 × 10 6 in 10 μL assay volume) and the low limit of detection (LOD) of 79 cells mL −1 (S/N = 3) were obtained. The LOD was lower than those values of most cytosensors reported so far, such as 794 HeLa cells mL −1 at aptamer-based impedance sensor 50 , 100 HeLa cells mL −1 at folic acid-based electrochemical cytosensor 51 , 90 HL-60 cells mL −1 at small-molecule ligand-based impedance sensor 52 , 620 BGC-823 cells mL −1 at enzyme-linked tetrapeptide-based sensor 53 and 1.8 × 10 4 Jurkat cells mL −1 at poly-lysine/GCE impedance sensor 54 ( Table S1 ). These results demonstrated that the covalent immobilization of specific phage led to highly efficient capture of tumor cells onto the electrode surface.…”
Section: Resultsmentioning
confidence: 99%